PENGARUH FREE CASH FLOW, INVESTMENT OPPORTUNITY SET, UKURAN PERUSAHAAN, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of variable free cash flow, investment opportunity set, firm size and managerial ownership of the debt policy on manufacturing companies listed in Indonesia Stock Exchange. This study uses agency theory and the pecking order theory. This study used purposive sampling and obtained a sample size of 140 companies listed in Indonesia Stock Exchange during 2010-2013. Data obtained from the Indonesian Capital Market Directory and Indonesian Directory Exchange. Data were analyzed using multiple regression analysis. The results showed that free cash flow is not a significant positive effect on debt policy, investment opportunity set is not a significant positive effect on debt policy, the size of the company significant positive effect on debt policy, and ownership manajeral significant negative effect on debt policy.Keywords: Free Cash Flow, Investment Opportunity Set, Firm Size, Managerial Ownership, Debt Policy